2008
DOI: 10.1136/ard.2007.082669
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking, disease severity and autoantibody expression in African Americans with recent-onset rheumatoid arthritis

Abstract: Objective-To examine the association of smoking with clinical and serologic features in African Americans with recent-onset rheumatoid arthritis (RA) and to explore whether this association is dependent on the presence of the HLA-DRB1 shared epitope (SE). Methods-InAfrican Americans with recent-onset RA (n = 300), we examined the association of cigarette smoking (current vs. past vs. never and pack-years of exposure) with anti-CCP antibody, rheumatoid factor (RF) (-IgM and -IgA), rheumatoid nodules, and baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 40 publications
9
34
0
2
Order By: Relevance
“…This suggests that it is associated with primary pathophysiological mechanisms 15 . In case RA smoking may increase the diseases severity, these associations were most pronounced in those with more than 20 pack-years of exposure Cigarette smoking is associated with both subcutaneous nodules and higher serum concentrations of IgA-RF in African Americans with RA, associations that may have important implications for long-term outcomes in this population 16 .…”
Section: Atypical Presentationmentioning
confidence: 98%
“…This suggests that it is associated with primary pathophysiological mechanisms 15 . In case RA smoking may increase the diseases severity, these associations were most pronounced in those with more than 20 pack-years of exposure Cigarette smoking is associated with both subcutaneous nodules and higher serum concentrations of IgA-RF in African Americans with RA, associations that may have important implications for long-term outcomes in this population 16 .…”
Section: Atypical Presentationmentioning
confidence: 98%
“…Another marker used for RA diagnosis is the anti-cyclic citrullinated peptide (CCP) antibody response [9]. Although some epidemiological studies have linked this response to smoking [10,11,14,15], this has not been confirmed in all studies [16].…”
Section: Introductionmentioning
confidence: 99%
“…Another marker used for RA diagnosis is the anti-cyclic citrullinated peptide (CCP) antibody response [9]. Although some epidemiological studies have linked this response to smoking [10,11,14,15], this has not been confirmed in all studies [16].Heat shock protein-70 (HSP70) encoded in the class III region of major histocompatibility complex (MHC) [17] is a stress response protein induced by heat and smoke exposure [18]. HSP70 is mainly expressed inside cells, but extracellular HSP70 (eHSP70) is found in serum although the physiological role(s) are yet to be established.…”
mentioning
confidence: 99%
“…Scoring was performed using state-of-the-art methods under the auspices of Désirée van der Heijde, a world expert in quantitative assessment of radiographs in rheumatic diseases (34). Furthermore, mTSS scores for participants from CLEAR I and CLEAR II have been validated extensively (35,36). from all three ethnicities using 8,138 genomic annotations (for example, DNAse hypersensitivity, enhancer markings and so on) provided with the PAINTOR3 algorithm; and (4) trimmed these to the top five uncorrelated annotations (correlation coefficient <0.10), excluding the annotations with lower Bayes factors.…”
Section: Study Populationmentioning
confidence: 99%